A Survey on Dynamic Data Delivery through Content Delivery Networks - Murari T, Vijaya; K.C.Ravishankar, Dr; ., . (International Journal of Engineering and Technology, 2018)
The growth of the internet users has been exponential over a period of time. This has led to the increased use of web for sharing content and services. Huge load on the bandwidth of the internet and the large number of requests for the content and services present in the website is due to the increased use of web for variety of purposes. This has restricted the ability of the internet to send the required data to the users in a time bound manner. The emergence of Content Delivery Networks (CDNâ€™s) has helped to alleviate these limitations by providing the necessary infrastructure and mechanisms to the internet. This paper focuses on CDNâ€™s, overview of CDNâ€™s, dynamic data delivery through CDN along with the merits and demerits, various Streaming Content Distribution Networks (SCDN) and challenges in streaming multimedia over CDN.Â